Fixed income markets and their derivatives - Sundaresan, Suresh M. (South-Western College, 1997)
An overview of Fixed-Income securities. Organization and conduct of debt markets. Treasury auctions and selling mechanisms. Bond mathematics. Yield-curve and term-structure analysis. No-arbitrage principle and the term structure. Options markets. Agency and corporate debt securities...